Pengaruh Motivasi, Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan Produksi Tali PT. Sumbertex di Kabupaten Batang - Viki Yuniarti; Hari Susanta Nugraha; Widiartanto Widiartanto (Universitas Diponegoro, 2016)
The company is trying to achieve the goals set by top management. The company’s goal include growth, profits, productivity, employee benefit, employee performance, and so on. The objective of this research is to investigate motivational influences, leaderships and compensations toward employee in rope producing performances PT.Sumbertex Batang either simultaneously and/or partially. This paper presents explanatory research seeking explanations and highlighting the relationship between the variables proposed in the research and explains the influence of the independent variables on the dependent variable. The research sample was taken from 76 people by using the formula solving with sampling technique Simple Random Sampling. The method of analysis of this research used validity, reliabilities, regression, t and F test. The result of multiple linear regression can be shown by the equation Y=7,286 +0,24X1+ 0,268 X2 + 0,212 X3. Partially magnitude of the effect of motivation on the performance of 46,6%, 45,5% leadership, and the compensation of 36,4%. Simultaneously the influence betwewn motivation, leadership and compensation to employee performance amounted to 47,2%. Suggestions presented in this study is to evaluate compensation systems for all the employees, both compensation that are financial or non-financial. Disseminate to employees the importance of adherence to the rules. In problems solving leaders should include employees, and conduct trainning job and evaluation at reguler intervals.